Analisis Deskriptif Kinerja Guru : Studi kasus pada SMP Negeri di Kabupaten Bandung - Romlah Romlah (Acman: Accounting and Management Journal, 2021)
This study aims to analyze the description of teacher performance. It uses descriptive analysis research methods to describe teacher performance, collecting data employing a survey on SMP Negeri teachers in Bandung Regency with the number of respondents as many as 32 teachers. The research result shows that the description of teacher performance is in the excellent category. The implication of the research results recommends that improve teacher performance, it is necessary to hold a school principal management workshop and to consider the aspirations of teachers, which are constructive as the basis for determining policies.